Effect of Genotype and Age on Egg Quality Traits in Naked Neck Chicken under Tropical Climate from India - Rajkumar, U.; Sharma, R.P.; Rajaravindra, K.S.; Niranjan, M.; Reddy, B.L.N.; Bhattacharya, T.K.; Chatterjee, R.N. (International Journal of Poultry Science, 2009)
A comprehensive study was undertaken to evaluate the egg quality traits in three naked neck genotypes, NaNa (homozygous), Nana (heterozygous) and nana (normal) by utilizing 556 eggs collected at 28, 32, 36 and 40 weeks of age. The overall mean egg weight, shape index and Haugh unit values were 56.41 g, 75.79 and 75.98, respectively. The yolk index, yolk height and yolk colour varied significantly (p